Self-Medication Practices among a Sample of Latino Migrant Workers in South Florida - Sánchez, Jesús (Frontiers in Public Health, 2014)
Introduction: Although the literature on self-medication among Latino migrant workers (LMWs) is sparse, a few existing studies indicate that this practice is common in this community. The purpose of this paper is to estimate health status, access to health care, and patterns of self-medication practices of a cohort of LMWs in South Florida. Methods: A stratified network-based sample was utilized to recruit 278 LMWs in the Homestead area. After screening for eligibility, participants were administered a structured questionnaire that collected data on their health status, access to health care services, and self-medication practices. A convenience sample of 24 Latino migrant workers who participated in the parent study were invited back to participate in 3 focus groups to look more in depth into self-medication practices in the Latino migrant worker community. Results: Study findings indicate that Latino migrant workers are affected by a vast array of health problems yet lack access to health care services. Participants already engaged in self-medication practices in the countries of origin and, upon their arrival in the US, these practices continue and, in many cases, increase. Conclusion: Long-held traditions and lack of access to the formal health care system in the US contribute to the high prevalence of self-medication among Latino migrant workers. Self-medication practices such as the use of prescription medications without a prescription and lay injection are high risk practices that can have harmful consequences. Prevention interventions that address self-medication in the Latino migrant worker community are likely to be most effective if they are culturally adapted to the community and facilitate access to health care services.